Development of economically viable waste tyre pyrolysis technologies that yield liquid fractions meeting commercial fuel standards - Khosa, Matimu (Stellenbosch : Stellenbosch University, 2025)
Khosa, M. 2025. Development of economically viable waste tyre pyrolysis technologies that yield liquid fractions meeting commercial fuel standards. Unpublished masters thesis. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/4e7c63fa-45a7-47de-b0f8-29cb85ee6701